DEVELOPING NUTMEG OIL DISTILLATION VIDEO AS AN ALTERNATIVE LEARNING MATERIAL FOR CRAFT AND ENTERPRENEUR SUBJECT MATTER IN SMAN 1 PASIE RAJA - Nayu Tisa; M Adlim; Ibnu Khaldun (Chimica Didactica Acta, 2022)
The purpose of this study was to develop a video of nutmeg oil distillation as an alternative material for craft and entrepreneurship subjects for class XI SMA N 1 Pasie Raja. This study  is research and development (RD) with the ADDIE model developed by Dick and Carry (1996). The videos that have been successfully made have gone through the ADDIE stage, namely validation by media experts and material experts with an average score of 88.9% and 88.5%, respectively, so that the material and media aspects are categorized as very good. The learning video is applied in the classroom by showing it; teachers and students gave positive responses of 100% and 88.14%, both of which were categorized as very good. The score of students' understanding of the learning video media obtained an average percentage of 79.47% and was categorized as good. Video learning of nutmeg oil refining is appropriate to be used as a medium of learning in the subjects of crafts and entrepreneurship.